Footsteps : from Ferrante's Naples to Hammett's San Francisco, literary pilgrimages around the world. (Three Rivers Press, 2017)
"A curated collection of the New York Times' travel column, "Footsteps," exploring classic authors' relationships to landmarks and cities around the world. Before The Sun Also Rises, Ernest Hemingway roamed the streets of Madrid, eager for the heady scent of blood emanating from the nearby bullrings. Before spunky, red-headed Anne Shirley stole readers' hearts in Anne of Green Gables, L.M. Montgomery was captivated by the sunset sky of Prince Edward Island. And before readers were terrified by a tentacled dragon-man called Cthulhu, H.P. Lovecraft was enthralled by the Industrial Trust tower-- the 26-story skyscraper that makes up the skyline of Providence, Rhode Island. Based on the popular New York Times travel column, Footsteps is an anthology of literary pilgrimages, exploring the geographic muses behind some of history's greatest writers. From the "dangerous, dirty and seductive" streets of Naples, the setting for Elena Ferrante's famous Neapolitan novels, to the "stone arches, creaky oaken doors, and riverside paths" of Oxford, the backdrop for Alice's adventures in Wonderland, Footsteps takes a fresh approach to literary tourism, appealing to readers and travel enthusiasts alike"--